Analisis Akuntabilitas Pengelolaan Keuangan - Duinkerken, Jessie Christy Natalia; Tinangon, Jantje J.; Budiarso, Novi Swandari (Gorontalo Accounting Journal, 2023)
This research aims to analyze the accountability of financial management of the North Sulawesi Provincial General Election Commission (KPU). The research method used is a qualitative approach. Data analysis involves data reduction, data display, and drawing conclusions. The research findings are as follows: (1) The financial management of the 2020 regional head election by the North Sulawesi Provincial General Election Commission was conducted in accordance with the Ministry of Finance regulations. (2) Several findings regarding the accountability of financial management of the North Sulawesi KPU for the 2020 regional head election were identified. (3) There are several efforts that need to be undertaken to enhance the accountability of financial management within the North Sulawesi Provincial General Election Commission.